Bloodstain Pattern: An open source of Evidence A Case Study: Muhammad Rashad Bhatti - Ayesha Sarwar; Bhatti, Muhammad Rashad Bhatti (International Journal for Electronic Crime Investigation, 2020)
Abstract:The purpose of this paper is to present a case study of a crime committed in a remote area of Pakistanwhere a woman was found dead and her death was reported as a suicide. Investigation agency collectedthe data including the pictures from the crime scene. These pictures were sent to crime scene unit fortheir recommendations. Forensic experts studied and analyzed these pictures and by applying thetechniques of Bloodstain Pattern Analysis (BPA). As blood behaves according to certain scientificprinciples, trained bloodstain pattern analysts can examine the blood evidence left behind and drawconclusions as to how the blood may have been shed. It is done by examining the distribution, location,shape and size of the bloodstains and it helps in determining about what did or did not happen. Becauseblood behaves according to certain scientific principles, trained bloodstain pattern analysts can examinethe blood evidence left behind [and draw conclusions as to how the blood may have been shed]. BPAprovides information not only about what happened, but just as importantly, what could not havehappened.A detailed analysis gave enough evidence to the experts that the submitted case was not a suicide rather itwas a case of a homicide. The paper will attempt to study the observations of experts while analyzing thebloodstain pattern submitted to them and the conclusions they subsequently drawn, leading towards aclear evidence of a murder case.